Nutrient requirements and growth physiology of the photoheterotrophic Acidobacterium, Chloracidobacterium thermophilum - Tank, Marcus; Bryant, Donald A. (Frontiers in Microbiology, 2015)
A novel thermophilic, microaerophilic, anoxygenic and chlorophototrophic member of the phylum Acidobacteria, Chloracidobacterium thermophilum strain BT, was isolated from a cyanobacterial enrichment culture derived from microbial mats associated with Octopus Spring, Yellowstone National Park, Wyoming. C. thermophilum is strictly dependent on light and oxygen and grows optimally as a photoheterotroph at irradiance values between 20 to 50 µmol photons m-2 s-1. C. thermophilum is unable to synthesize branched-chain amino acids, L-lysine, and vitamin B12, which are required for growth. Although the organism lacks genes for autotrophic carbon fixation, bicarbonate is also required. Mixtures of other amino acids and 2-oxoglutarate stiumulate growth. As suggested from genomic sequence data, C. thermophilum requires a reduced sulfur source such as thioglycolate, cysteine, methionine, or thiosulfate. The organism can be grown in a defined medium at 51°C (Topt; range 44 to 58°C) in the pH range 5.5 to 9.5 (pHopt = ~7.0). Using the defined growth medium and optimal conditions, it was possible to isolate new C. thermophilum strains directly from samples of hot spring mats Yellowstone National Park, Wyoming. The new isolates differ from the type strain with respect to pigment composition, morphology in liquid culture, and temperature adaptation.